Pengembangan LKPD Berbasis Cryptarithm untuk Meningkatkan Kemampuan Berpikir Logis Matematis (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The purpose of this research is to describe the development process of Student Worksheets based on cryptarithm that can enhance logical thinking abilities and to determine the validity and practicality results of the developed product. Cryptarithm is a means to develop students' logical thinking skills in the context of mathematics. The logical structure in cryptarithm encourages students to develop logical thinking skills. Students must be able to identify mathematical patterns and use logic to limit the possibility of substituting numbers for existing letters. This research is a development study using the R&D method. The development model used is ADDIE, which includes analyze, design, development, implementation, and evaluation. The testing was conducted in two stages: a limited trial with 5 students and a broad-scale trial with 20 students. The research results indicate that the student worksheets is valid with a percentage score of 98.33% and can be considered practical for use by students as an effort to improve mathematical logical thinking abilities, with a practicality score of 87.13%. Based on these results, it can be concluded that the Cryptarithm-based student worksheets developed to enhance mathematical logical thinking abilities is categorized as Highly Valid and Highly Practical